A swim through the sea - Pratt-Serafini, Kristin Joy. (Nevada City, CA : Dawn, 1994)
Explores the fascinating plants and animals of the undersea world including the clownfish, the hermit crab, dolphins and whales, and the queen conch.
Book Links (A.L.A.)
Horn Book
School Library Journal
5.2
3-6
3-6
Keywords: Marine animals -- Juvenile literature; Marine biology -- Juvenile literature; Marine plants -- Juvenile literature; Marine animals; Marine biology; Marine plants; Marine animals; Marine biology; Marine plants